2018
DOI: 10.1111/jonm.12654
|View full text |Cite
|
Sign up to set email alerts
|

Nurse absenteeism: An analysis of trends and perceptions of nurse unit managers

Abstract: An analysis of absenteeism trends will assist management in initiating tailor-made intervention measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 24 publications
2
37
0
8
Order By: Relevance
“…The use of objective working‐hour data within 28 days preceding short sickness absence and utilization of case‐crossover design enabled us to control several factors potentially influencing the associations of working‐hour characteristics and short sickness absence, such as organisation, work culture and environment. Although shift work and ageing may be associated with higher risk for long sickness absence as shown in an earlier study based on partially the same data but also by others (Ropponen et al, 2019; Ticharwa et al, 2019), our results suggest that age does not directly affect the association of specific working‐hour characteristics with short sickness absence. An additional finding for practical significance was that strenuous working time characteristics are less frequent among the ageing confirming our hypothesis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The use of objective working‐hour data within 28 days preceding short sickness absence and utilization of case‐crossover design enabled us to control several factors potentially influencing the associations of working‐hour characteristics and short sickness absence, such as organisation, work culture and environment. Although shift work and ageing may be associated with higher risk for long sickness absence as shown in an earlier study based on partially the same data but also by others (Ropponen et al, 2019; Ticharwa et al, 2019), our results suggest that age does not directly affect the association of specific working‐hour characteristics with short sickness absence. An additional finding for practical significance was that strenuous working time characteristics are less frequent among the ageing confirming our hypothesis.…”
Section: Discussionsupporting
confidence: 71%
“…Our earlier studies, based on the Finnish Public Sector study, indicated that long working hours, several consecutive night shifts and short (<11 hr) recovery periods between the shifts are associated especially with short (1–3 days) sickness absence (Ropponen et al, 2019) but also with fatigue and sleep disturbances (Härmä, Karhula, Puttonen, et al, 2018; Härmä, Karhula, Ropponen, et al, 2018). Yet, these studies did not investigate age group differences, and it could be assumed that younger and older workers in female‐dominated social and health sector might react differently for working‐hour characteristics, and consequently, rates of sickness absence could differ (Cai et al, 2019; Stock et al, 2019; Ticharwa, Cope, & Murray, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…14 , 23 We assumed baseline 3% nurse absenteeism and an additional 8% absenteeism for the SARS-CoV-2 pandemic months. 24 , 25 To place results within the global context, we used median number of vaccinators per capita from other WHO regions calculated similarly. For the monthly comparisons and time series, we assumed constant routine immunization demand throughout the year and constant SARS-CoV-2 immunization demand during a mass vaccination campaign of four months duration.…”
Section: Methodsmentioning
confidence: 99%
“…10 d. Adjustments account for 3% absenteeism (baseline) and an additional 8% absenteeism (during pandemic). 24 , 25 …”
Section: Figurementioning
confidence: 99%
“…1,2 It has a multi-factorial etiology and can be divided into three areas: personal factors, such as age, family characteristics and quality of life; organizational factors, such as job satisfaction and leadership; and factors related to the workplace, such as overload of activities and quality of the work environment. 3,4 Identifying the direct influence of the quality of the work environment on absenteeism is essential, since this knowledge provides subsidies for the management of health institutions to promote actions that result in improving the quality of the environment, whether with improvements in infrastructure, dimensioning of human resources and organizational culture; so that the worker's health is not affected, increasing job satisfaction, reducing absenteeism and, consequently, improving quality of care.…”
Section: Introductionmentioning
confidence: 99%